Neonatal sepsis: a systematic review of core outcomes from randomised clinical trials - Henry, Cían J; Semova, Gergana; Barnes, Ellen; Cotter, Isabel; Devers, Tara; Rafaee, Aisyah; Slavescu, Andreea; Cathain, Niamh O; McCollum, Danielle; Roche, Edna; Mockler, David; Allen, John; et al. (Pediatric research, 2022)
BACKGROUND: The lack of a consensus definition of neonatal sepsis and a core outcome set (COS) proves a substantial impediment to research that influences policy and practice relevant to key stakeholders, patients and parents. METHODS: A systematic review of the literature was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. In the included studies, the described outcomes were extracted in accordance with the provisions of the Core Outcome Measures in Effectiveness Trials (COMET) handbook and registered. RESULTS: Among 884 abstracts identified, 90 randomised controlled trials (RCTs) were included in this review. Only 30 manuscripts explicitly stated the primary and/or secondary outcomes. A total of 88 distinct outcomes were recorded across all 90 studies included. These were then assigned to seven different domains in line with the taxonomy for classification proposed by the COMET initiative. The most frequently reported outcome was survival with 74% (n = 67) of the studies reporting an outcome within this domain. CONCLUSIONS: This systematic review constitutes one of the initial phases in the protocol for developing a COS in neonatal sepsis. The paucity of standardised outcome reporting in neonatal sepsis hinders comparison and synthesis of data. The final phase will involve a Delphi Survey to generate a COS in neonatal sepsis by consensus recommendation. IMPACT: This systematic review identified a wide variation of outcomes reported among published RCTs on the management of neonatal sepsis. The paucity of standardised outcome reporting hinders comparison and synthesis of data and future meta-analyses with conclusive recommendations on the management of neonatal sepsis are unlikely. The final phase will involve a Delphi Survey to determine a COS by consensus recommendation with input from all relevant stakeholders.
Keywords: delfská metoda; novorozenec; Infant, Newborn; Neonatal Sepsis; novorozenecká sepse; Research Design; randomizované kontrolované studie jako téma; výsledek terapie; Humans; lidé; Randomized Controlled Trials as Topic; Outcome Assessment, Health Care; Delphi Technique; Treatment Outcome; hodnocení výsledků zdravotní péče; výzkumný projekt